Associational Effects and Indirect Interactions-The Dynamical Effects of Consumer and Resource Traits on Generalist-Resource Interactions - Klapwijk, Maartje J.; Bonsall, Michael B. (Frontiers in Ecology and Evolution, 2022)
Trophic interaction modifications occur in food webs when the direct or indirect interaction between two species is affected by a third species. These behavioural modification effects are often referred to as associational effects. Changes in focal resource availability and consumption by the generalist can affect a range of dynamical outcomes from resource exclusion to multiple resources coexisting. Here, we investigate the interactions between a focal and alternative resource mediated by a generalist consumer. Using theoretical approaches we analyse the conceptual link between associational effects and the theory of apparent competition and resource switching. We find that changes in focal resource traits have the potential to affect the long-term outcome of indirect interactions. Inclusion of density-dependence expands generalist life-histories and broadens the range where, through associational effects, the availability of alternative resources positively influence a focal resource. We conclude that different forms of associational effects could, in the long-term, lead to a range of indirect interaction dynamics, including apparent competition and apparent mutualism. Our work connects the theoretical body of work on indirect interactions to the concepts of associational effects. The indirect interactions between multiple resources need more thorough investigation to appreciate the range of associational effects that could result from the dynamical interaction between a generalist consumers and its focal and alternative resources.